Effects of zymotic fluid of Cordyceps sinensis mycelium on the immune function of Rex Rabl rabbit - CAO Zhuoyang; LÜ Qinghua; XIE Yuan; FANG Ping; WANG Rongcai; YE Dafeng (浙江大学学报. 农业与生命科学版)
In order to investigate the effect of Cordyceps sinensis mycelium on the immune function of Rex Rabl rabbit, feeding experiments were carried out on mother Rex Rabl rabbits and their weaning young rabbits with the additive of zymotic fluid of C. sinensis mycelium. In the experiment of mother rabbit, 80 pregnant Rex Rabl rabbits of similar body mass were randomly divided into two groups. Between them, the control group was fed with basal diet and the treatment group with improved diet (added 2% zymotic fluid of C. sinensis mycelium based on basal diet). In the experiment of weaned young rabbit, the treatment groupⅠwith 10 offsprings from the previous treatment group and the treatment group Ⅱ with 10 offsprings from the previous control group were both fed with improved diets, and the control group with 10 offsprings from the previous control group was fed with basal diet. The results of mother rabbit experiment showed that the survival rate of young rabbits of the treatment group was significantly higher than that of the control group by 28 percentage points (P<0.01), and the overall death rate of the treatment group was significantly lower than that of the control group by 33.5 percentage points (P<0.05). Moreover, the IgA content of lactating female rabbits in the treatment group was significantly higher than that in the control group (P<0.01). The results of weaning young rabbit experiment indicated that the rabbit appendix index of the treatment groupⅠwas significantly higher than that of the control group, and the positive rates of T lymphocytes in the treatment groupⅠand Ⅱ were significantly enhanced in comparison to that in the control group (P<0.01). In conclusion, feeding the mother rabbits in pregnancy and lactation with improved diet containing zymotic fluid of C. sinensis mycelium is helpful to reduce the infant rabbit mortality and increase the IgA content of mother rabbit. Feeding the weaning rabbits with improved diet is also beneficial to enhance immune organ mass and positive rate of T lymphocyte of young rabbits. This study indicates that the immune function and disease-resistant ability of Rex Rabl rabbits can be enhanced by adding zymotic fluid of C. sinensis mycelium in basal diet.